Development of IPTA affecting the surrounding area case study: University Utara Malaysia / Norshuhada Abdul Rahim - Abdul Rahim, Norshuhada (Faculty of Architecture, Planning and Surveying, 2010)
Higher learning institutional is one of the organizations which play the important rule to perform a new generation with high education. Beside that, the development of higher learning institution can also generate the development of the surrounding area. It will act as the catalyst to the surrounding area development. Usually, activities like business and services such as industry and commercial help to increase the development. But, the development of highest educational institution also can be a catalyst to develop the rural area. The development directly will change the physical condition of the area and society. So, this research is done to identify the types of development exist after the development of IPTA and also it effect to the surrounding area. All the data collected from related department and also interview. It is hoped that this academic final project could clearly shows and explain the effect of the development of IPTA to the surrounding area. It is also hoped that this research can be useful to the local authority in order to develop this area and become one of the well known area